Sequence learning enhancement following single-session meditation is dependent on metacontrol mode and experienced effort - Immink, M. A.; Colzato, L. S.; Stolte, M.; Hommel, B. (Journal of Cognitive Enhancement, 2017)
Focused attention (FAM) and open monitoring (OMM) meditation types establish distinct metacontrol states that have immediate effects on how attention allocation strategies are utilised in subsequent, unrelated tasks. Because attention allocation is a central factor in sequential action, the present experiment investigated whether a single-session of FAM and OMM enhanced subsequent sequence performance and learning. Relative to a control listening task, a single session of FAM or OMM resulted in heightened sequence performance without affecting sequence learning on average. However, the level of effort experienced in the meditation conditions was found to significantly correlate with sequence learning indices and post hoc analyses revealed that low effort level in both meditation groups was associated with significantly greater general sequence performance improvements. Interestingly, the degree of sequence-specific learning that brought about these improvements was enhanced only by OMM and only in those reporting low effort level with this meditation type. Thus, only the combination of low effort and OMM established a cognitive control state that was beneficial for the acquisition of complex sequence structures. This work provides further insights into instantaneous effects of FAM and OMM on goal-oriented cognitive function while also raising important questions about the control of mediation-induced states.